Pelatihan Orientasi Kewirausahaan Untuk Meningkatkan Keinovasian Pada Usaha Makanan Tradisional Di Desa Sindurejo, Kecamatan Toroh, Kabupaten Grobogan - Sri Wahyuni; Sunarto Sunarto; Muhammad Sabandi; Villa Santika (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2018)
This program is carried out on Small and Medium Enterprises (SME) Suka Rasa and SME Sendang Rasa in Toroh District, Grobogan Regency. Both SMEs have the same characteristics of business and products, namely tempe chips and banana chips. The weakness of this SMEs is the packaging of products and ways of marketing that are very simple. Their behavior of business has not shown the attitudes of an entrepreneur, so the performance of SMEs is still low. Making product innovation was the aims of this community service program, for improving the knowledge and ability of entrepreneurship orientation of SMEs. The method used to develop an entrepreneurial orientation in this activity is using training and product innovation practices. The success of this activity was measured through perceptions of innovation and product sales performance. The result of this activity was shown a big change on the behavior of SMEs, that is becoming more entrepreneur oriented, such as: 1) SMEs have made innovation by experimenting the products of chips into various flavor variants, such as saltiness, barbeque flavor, and cheese flavor; 2) SMEs have been able to recognize the risks faced when innovating products; 3) SMEs can able to map competitors and market potential. The packaging design and P-IRT licenses on products produced by SMEs were an additional output for this program.